Strong T-cell activation in response to COVID-19 vaccination in multiple sclerosis patients receiving B-cell depleting therapies - Alfonso-Dunn, Roberto; Lin, Jerry; Kirschner, Vanessa; Lei, Joyce; Feuer, Grant; Malin, Michaela; Liu, Jiayuan; Roche, Morgan; Sadiq, Saud A. (Frontiers in Immunology, 2022)
Immunocompromised individuals, including multiple sclerosis (MS) patients on certain immunotherapy treatments, are considered susceptible to complications from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and specific vaccination regimens have been recommended for suitable protection. MS patients receiving anti-CD20 therapy (aCD20-MS) are considered especially vulnerable due to acquired B-cell depletion and impaired antibody production in response to virus infection and COVID-19 vaccination. Here, the humoral and cellular responses are analyzed in a group of aCD20-MS patients (n=43) compared to a healthy control cohort (n=34) during the first 6 months after a 2-dose cycle mRNA-based COVID-19 vaccination. Both IgG antibodies recognizing receptor binding domain (RBD) from CoV-2 spike protein and their blocking activity against RBD-hACE2 binding were significantly reduced in aCD20-MS patients, with a seroconversion rate of only 23.8%. Interestingly, even under conditions of severe B-cell depletion and failed seroconversion, a significantly higher polyfunctional IFNγ+ and IL-2+ T-cell response and strong T-cell proliferation capacity were detected compared to controls. Moreover, no difference in T-cell response was observed between forms of disease (relapsing remitting- vs progressive-MS), anti-CD20 therapy (Rituximab vs Ocrelizumab) and type of mRNA-based vaccine received (mRNA-1273 vs BNT162b2). These results suggest the generation of a partial adaptive immune response to COVID-19 vaccination in B-cell depleted MS individuals driven by a functionally competent T-cell arm. Investigation into the role of the cellular immune response is important to identifying the level of protection against SARS-CoV-2 in aCD20-MS patients and could have potential implications for future vaccine design and application.